SIMILARITY MEASURE BETWEEN INTERVAL-VALUED INTUITIONISTIC FUZZY SETS AND THEIR APPLICATIONS TO MEDICAL DIAGNOSIS AND PATTERN RECOGNITION - DHIVYA, J.; SRIDEVI, B. (International Journal of Mathematical Archive, 2018)
In this paper, we present an effective method for evaluating similarity measure between Interval-valued Intuitionistic Fuzzy set (IVIFS) based on the mid points of transformed triangular fuzzy numbers. Some relevant properties of the proposed similarity measures are discussed and the related similarity measures are also compared. Several illustrative examples are given to demonstrate the practicality and effectiveness of the proposed similarity measure. Further, in order to provide the supportive evidence, the proposed similarity measure is applied for medical diagnosis problem and Pattern Recognition problem and to demonstrate benefits of using the proposed similarity measure over the existing ones.